Hypertensive crises in patients with essential arterial hypertension and coronary heart disease: new perspectives in treatment and prevention - A. P. Golikov; M. M. Lukjanov; V. Yu. Polumiskov; P. P. Golikov; B. V. Davydov; D. V. Rudnev (Кардиоваскулярная терапия и профилактика)
Aim. To study clinical efficacy of hypertensive crise (HC) complex therapy and prevention in patients with combination of essential arterial hypertension (EAH) and coronary heart disease (CHD), at hospital and posthospital levels. Complex management program included treatment with antioxidant-cytoprotector, Mexicor®, as well as 24-hour blood pressure monitoring (BPM), ECG monitoring, and various BP self-monitoring variants. Material and methods. In total, 157 patients with HC, EAH, and CHD, were examined. The participants were randomized into three groups: standard post-hospital follow-up (Group A, n=45); BP self-monitoring, without (Group B, n=54) or with (Group C, n=58) weekly telephone control by a doctor, and correction of therapy regimen, if necessary. At hospital and post-hospital levels, 20 patients from group B (sub-group B1), and 20 patients from group C (sub-group C1), were additionally administered antioxidant-cytoprotector. Post-hospital follow-up time varied from 1 month (uncomplicated HC) to 2-3 months (HC with cardiac complications). Treatment efficacy assessment included bi-functional 24-hour BPM and ECG monitoring at Day 1, Day 7-10, and Day 40-50 of the follow-up. Results. Among patients with HC and CHD, BP self-monitoring and dynamic medical control facilitated BP normalization (83.1%), and decrease in post-hospital incidence of pre-crise states or recurrent HC (5.2% and 1.7%), compared to standard post-hospital follow-up – 68.9%, 20.0%, and 11.1%, respectively. Adding to complex hospital and post-hospital management was associated with BP normalization, decrease in total cardiovascular event risk, and reduction in pre-crise state or recurrent HC incidence. Conclusion. Efficacy of HC treatment and prevention in patients with EAH and CHD was improved by posthospital BP self-monitoring and additional administration of antioxidant-cytoprotector.